Endovascular Thrombectomy of Calcified Emboli in Acute Ischemic Stroke: A Multicenter Study - Maurer, C.J.; Dobrocky, T.; Joachimski, F.; Neuberger, U.; Demerath, T.; Brehm, A.; Cianfoni, A.; Gory, B.; Berlis, A.; Gralla, J.; Möhlenbruch, M.A.; Blackham, K.A.; et al. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Large intracranial vessel occlusion due to calcified emboli is a rare cause of major stroke. We assessed the prevalence, imaging appearance, the effectiveness of mechanical thrombectomy, and clinical outcome of patients with large-vessel occlusion due to calcified emboli.MATERIALS AND METHODS: We performed a retrospective analysis of clinical and procedural data of consecutive patients who underwent mechanical thrombectomy due to calcified emboli in 7 European stroke centers.RESULTS: We screened 2969 patients, and 40 patients matched the inclusion criteria, accounting for a prevalence of 1.3%. The mean maximal density of the thrombus was 327 HU (range, 150–1200 HU), and the mean thrombus length was 9.2 mm (range, 4–20 mm). Four patients had multiple calcified emboli, and 2 patients had an embolic event during an endovascular intervention. A modified TICI score of ≥2b was achieved in 57.5% (23/40), with minimal-to-no reperfusion (modified TICI 0–1) in 32.5% (13/40) and incomplete reperfusion (modified TICI 2a) in 10% (4/40). Excellent outcome (mRS 0–1) was achieved in only 20.6%, functional independence (mRS 0–2) in 26.5% and 90-day mortality was 55.9%.CONCLUSIONS: Acute ischemic stroke with large-vessel occlusion due to calcified emboli is a rare entity in patients undergoing thrombectomy, with considerably worse angiographic outcome and a higher mortality compared with patients with noncalcified thrombi. Good functional recovery at 3 months can still be achieved in about a quarter of patients.CLASScalcium load assessmentMTmechanical thrombectomymTICImodified TICI